Application of HIS-based medical consumables management system in nursing management in the Department of Stomatology (基于HIS系统的医用耗材管理在口腔科护理管理中的应用) - DING Shanshan (丁珊珊); WU Xuan (吴宣); GAN Ling (甘泠) (中西医结合护理)
Stomatological consumable inventory is notoriously difficult to track. This paper summarized the development and application of Hospital Information System-based medical consumables management in nursing management in the Department of Stomatology. Components of the system, operator interface, operating procedure and advantages of system were analyzed. HIS-based medical consumables management could say the human resource and improve the working efficiency in a scientific, effective and accurate way. (口腔科耗材繁琐, 管理难度大。本研究就基于HIS系统的医用耗材管理系统的研发和应用进行总结, 包括系统的组成、操作界面、操作流程以及系统优势等, 通过对口腔科医用耗材进行科学、有效、准确地管理, 节约人力资源, 提升工作效率。)